The Impact of Perioperative Blood Pressure on Hematoma Development After Panniculectomy. Issue 5 (June 2021) - Rudolph, Megan; Galazra, Laura; Greer, Madison; Hemal, Kshipra; Runyan, Christopher
Abstract : Purpose: Hematoma affects 10% to 13% of patients undergoing panniculectomy. Although elevated perioperative blood pressure has been associated with hematoma after rhytidectomy, this has not been established for panniculectomy. We sought to determine the impact of perioperative blood pressure on hematoma development in patients undergoing panniculectomy. Methods: A retrospective review was performed on patients undergoing isolated panniculectomy procedures. Blood pressure parameters recorded included systolic blood pressures (SBPs), diastolic blood pressures (DBPs), and mean arterial pressure. The mean, peak, and trough blood pressure values were recorded. Preoperative, intraoperative, and postoperative blood pressures were recorded, and differences between phases were calculated. Univariate and multivariate logistic regressions were performed. Results: One hundred forty-three patients were identified, which included 84% (n = 120) women and 17% (n = 23) men. A history of hypertension was present in 55% (n = 79) of patients, of which 91% (n = 72) were medically controlled. Preoperative antiplatelet or anticoagulation was used in 21% (n = 31) of patients. Seven patients (5%) developed a hematoma, of which 5 required operative drainage. Development of hematoma was not associated with patient, surgical, or postoperative pain variables. There was an association between hematoma and elevated postoperative blood pressures on univariate and multivariate analyses. The mean peak SBP in the hematoma group was 160 mm Hg in comparison to 141 mm Hg in the nonhematoma group. For each 10-mm Hg increase in postoperative peak SBP, the odds of a hematoma increased by 2.8 times. When comparing phases of care, hematoma patients had similar intraoperative and postoperative peak SBP, but their postoperative SBP was 19 mm Hg higher than preoperative baseline. Conversely, nonhematoma patients had a postoperative blood pressure that was similar to their preoperative baseline and 20 mm Hg lower than their intraoperative values. Conclusions: Hematoma is associated with elevated postoperative blood pressures. A postoperative mean peak SBP of 160 mm Hg was associated with hematoma, and for each 10 mm Hg, the risk of hematomsa increased by 2.8 times. The risk of hematoma may be reduced by strict postoperative blood pressure control. We recommend a postoperative peak SBP goal of 140 mm Hg or less, with a value equal to or less than their preoperative baseline and 20 mm Hg lower than their intraoperative pressure.